Energetics and Water Flux in the Subterranean Rodent Family Bathyergidae - Hart, Daniel W.; Bennett, Nigel C.; Oosthuizen, Maria K.; Waterman, Jane M.; Hambly, Catherine; Scantlebury, David M. (Frontiers in Ecology and Evolution, 2022)
The doubly labelled water (DLW) technique and indirect calorimetry measurement enable measurement of the daily energy expenditure (DEE, kJ/day), resting metabolic rate (RMR, kJ/d), sustained metabolic scope (SusMS), body fat content (BF, %) as well as water turnover (WTO, ml/day), and water economy index (ml/kJ). Small mammals have been the primary focus of many of the DLW studies. From large multi-species analysis of the energetics and water flux of aboveground small mammals, well-defined trends have been observed. These trends mainly refer to an adaptive advantage for lower RMR, DEE, SusMS, WTO and WEI in more arid dwelling animals to increase water and energy savings under low and unpredictable resource availability. The subterranean rodent family Bathyergidae (African mole-rats) has been an area of particular interest with regards to field metabolic rate and metabolic studies. Although a great deal of research has been conducted on the family Bathyergidae, a complete overview and multi-species analysis of the energetics and water flux of this family is lacking. Consequently, we assessed DEE, RMR, SusMS, BF, WTO and WEI across several different species of bathyergids from various climatic regions, and we compared these to the well-known patterns of energetics and water flux for above ground rodents. There was notable variation across the family Bathyergidae inhabiting areas with different aridities, often contrary to the variations in aboveground species. These include increased DEE and WEI in arid-dwelling bathyergid species. While the climate was not a factor when predicting the SusMS of a bathyergid species, rather the degree of group living was the primary driver of SusMS, with solitary species possessing the highest SusMS compared to the socially living species. We conclude that the underground lifestyle and spectrum of social behaviours possessed by the family Bathyergidae are most likely more crucial to their energetics and water flux than their habitat; however other important unstudied factors may still be at play. More so, this study provides evidence that often unreported parameters, measured through use of the DLW technique (such as BF and WEI) can enable species to be identified that might be at particular risk to climate change.